Implementation of the Jigsaw Type Cooperative Learning Model to Improve Learning Outcomes of Outside Foot Passing in Soccer Games - Mohamad Dani Sawaludin; Bahmid Hasbullah; Johanna Matitaputty (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2026)
This study aims to improve the learning outcomes of passing skills using the outside of the foot in soccer games through the application of the Jigsaw cooperative learning model. The study used the Classroom Action Research (CAR) method which was implemented in two cycles, including the planning stage, action implementation, observation, and reflection. The research subjects were 30 seventh-grade students of SMP Negeri 15 Ambon. Data were collected through skills tests, observation, and documentation, then analyzed descriptively based on the percentage of learning completion with a Minimum Completion Criteria (KKM) of 76. The results showed that the application of the Jigsaw cooperative learning model was able to improve student learning outcomes. The percentage of learning completion increased from 40% (12 students) in Cycle I to 100% (30 students) in Cycle II. In addition, there was an increase in student activity, cooperation, responsibility, and self-confidence during the learning process. This increase was followed by improvements in passing techniques using the outside of the foot, including body position, placement of the supporting foot, movement coordination, and accuracy of the ball direction. Thus, the Jigsaw type cooperative learning model is effective in improving learning outcomes of passing skills using the outside of the foot in soccer learning in junior high schools